Modeling E-Government adoption: trust, perceived risk and political efficacy - Hussein, Ramlah; Mohamed, Norshidah; Ahlan, Abdul Rahman; Mahmud, Murni (2010)
The rapid development of ICT and Internet Technology has encouraged governments to take part in the virtual world through the development and deployment of electronic government or e-government in order to better serve the citizens. As one of the MSC Malaysia Flagship Applications, e-government initiative has been introduced since ten years ago aiming at building a more effective and efficient way to communicate and transact with the citizens and industries. One of the projects is Online Tax System or e-Filing that has gained its popularity since it was launched in 2006. But the obstacles remain concern taxpayers who are really anxious about the technology, lacking of technical skills, or do not trust of any online transaction. This has led the researchers to investigate the factors that might contribute to taxpayer’s intention to use e-Filing system. Against this backdrop, this research intends to study about Government to Citizens (G2C) adoption in Malaysia by integrating the Technology Acceptance Model (TAM) theory, Diffusion and Innovation (DOI) theory and Perceived Characteristics of Innovating (PCI) as a research framework. Other factors that are believed in influencing citizens’ intention to use G2C system are also examined in the study they are social influence, web-based service quality, trust of the internet, trust of the government, and perceived risk. The results demonstrate that trust of the government and web-based service quality are found to be a significant factors influencing citizens’ intention to use e-Filing. Key implications for theory and practice are also discussed.